Eu3+-Postdoped UIO-66-Type Metal–Organic Framework as a Luminescent Sensor for Hg2+ Detection in Aqueous Media - Xiaoxiong, Zhang; Wenjun, Zhang; Cuiliu, Li; Xiaohong, Qin; Chengyu, Zhu (Inorganic chemistry, 2019)
Because of its extreme toxicity, the determination of Hg2+ in aqueous solution is an important subject for human health and environmental monitoring. In this study, a novel UIO-66-type metal–organic framework (MOF) doped with Eu3+ (isophthalic acid and 2,6-pyridinedicarboxylic acid and zirconium chloride served as the organic connectors and metal precursor, respectively) was prepared by a hydrothermal method and postsynthetic modification. The obtained lanthanide MOFs exhibited good photothermal and fluorescence stability in aqueous solution. As a luminescent probe, dispersions of the material can specifically recognize Hg2+ in many ions and have a detection limit of 8.26 nM. This novel lanthanide MOF shows great potential applications for biosensing, imaging, environmental analysis, and so on.